Meta-Analysis: Effect of Transport Distance on Physiological Conditions, Pre-Slaughter, and Broiler Meat Quality - Teysar Adi Sarjana; Raditya Putra Adiwangsa; Rina Muryani (Universitas Bengkulu, 2022)
Meta-analysis study of the effect of transportation distance on physiological conditions, pre-slaughter and broiler meat quality was carried out to examine the magnitude of the effect and calculate the publication bias of the effect of transportation distance on physiological conditions, pre-slaughter and broiler meat quality. The materials obtained from 1123 studies and 622 relevant studies were selected from 62 journals for further analysis. Parameters observed related to physiological conditions consisted of blood glucose levels, corticosterone levels, and body temperature. Parameters of pre-slaughter conditions on arrival were observed from weight loss and mortality. Meat quality parameters were observed from the percentage of drip loss, pH, and meat color. Transportation distances are categorized into various moderator individual and combined distances, namely <60 km, 60-180 km, >180 km and combined distances (a collection of distances <60 km, 60-180 km, and >180 km). The data obtained were tabulated and analyzed using CMA 3.7 software. The results showed a negative effect of transportation distances on physiological conditions, pre-slaughter and broiler meat quality with a moderate level of determination (est. 0.3-0.5) to strong on the parameters of physiological conditions, pre-slaughter and broiler meat quality. (est. 0.5-1.0). Publication bias was found in several parameters such as corticosterone levels and color (redness) did not show a significant egger's test result (p>0.05), which are potentially having an interfere with the interpretation of the study results. However the significant results of the Rosenthal analysis (p<0.05)) means that the intervention did not change the overall interpretation of the data. It concluded that transportation distance had a negative effect on physiological conditions, pre-slaughter and broiler meat quality with a moderate to strong effect and the consistency of publication results.